Urease Activity Level in Crude Extract From Peels of Some Legumes and Cucurbits - Zainab M. Dahham (Journal of Global Pharma Technology, 2020)
Ureases are an important group of enzymes with various applications in the analysis of food and water, chemicals, clinical, agricultural and pharmaceutical industry, besides having great interest for the treatment the industrial waste. The main objective of the present project is to extract urease enzyme from economical sources which can be utilized in biotechnology, medicine and industrial fields, as well as clean the environment from the plant wastes and recycle it. In this study urease was extracted from peels of some legumes and cucurbits: (bean, pea, water melon and melon), as well as bean seeds were also used as a known main source of urease for comparison. The enzyme was extracted from peels by electrical blender homogenization with phosphate buffer (0.2 M, pH 7), then protein concentration, urease activity, pH stability, thermal stability and storage stability were determined in crude extract. Urease activity and specific activity extracted from pea peels was the highest among the other extracted wastes, which showed stability at neutral pH 7 at room temperature, also it was very stable when incubated at (40-50 °C) for 20 min, and during storage at -18 °C at pH 7 for 3 months indicating that this enzyme was very stable. No significant differences were found between urease activity using pea peels with that measured by standard kit for the blood urea determination in serum of normal and patients. So, pea peels considered as an important economic source of urease enzyme.Keywords: Urease activity, Pea peels, PH stability, Thermal stability.